Body Composition Changes During a 24-h Winter Mountain Running Race Under Extremely Cold Conditions - Chlíbková, Daniela; Žákovská, Alena; Rosemann, Thomas; Knechtle, Beat; Bednář, Josef (Frontiers in Physiology, 2019)
Background: To date, no study has focused on body composition characteristics and on parameters associated with skeletal muscle damage and renal function in runners participating in a 24-hour winter race held under extremely cold environmental conditions (average temperature of -14.3°C). Methods: Anthropometric characteristics, plasma urea (PU), plasma creatinine (Pcr), creatine kinase (CK), plasma volume (PV) and total body water (TBW) were assessed pre- and post-race in 20 finishers (14 men and 6 women). Results: In male runners, body mass (BM) (p = 0.003) and body fat (BF) (p = 0.001) decreased [-1.1 kg (-1.4%) and -1.1 kg (-13.4%), respectively]; skeletal muscle mass (SM) and TBW remained stable (p ˃ 0.05). In female runners, BF decreased (p = 0.036) [-1.3 kg (-7.8%)] while BM, SM and TBW remained stable (p ˃ 0.05). The change (∆) in BM was not related to ∆ BF; however, ∆ BM was related to ∆ SM [r = 0.58, p = 0.007] and ∆ TBW (r = 0.59, p = 0.007). ∆ SM correlated with ∆ TBW (r = 0.51, p = 0.021). Moreover, ∆ BF was negatively associated with ∆ SM (r = -0.65, p = 0.002). PV (p ˂ 0.001), CK (p ˂ 0.001), Pcr (p = 0.004) and PU (p ˂ 0.001) increased and creatinine clearance (CrCl) decreased (p = 0.002). The decrease in BM was negatively related to the increase in CK (r = -0.71, p ˂ 0.001). ∆ Pcr was positively related to ∆ PU (r = 0.64, p = 0.002). The decrease in CrCl was negatively associated with the increase in both PU (r = -0.72, p < 0.001) and CK (r = -0.48, p = 0.032). Conclusions: The 24-hour running race under extremely cold conditions led to a significant BF decrease, whereas SM and TBW remained stable in both males and females. Nevertheless, the increase in CK, Pcr and PU was related to the damage of SM with transient impaired renal function.